SUSTAINABLE COUNSELLING VALUES BY INDONESIAN PRESCHOOL TEACHERS TO PREPARE MORE TOLERANT YOUNG GLOBAL CITIZENS - Solehuddin, M. (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
Issues of intolerance in Indonesia, even involving children, have become the concerns of all related agencies, particularly those in children?s education. Although character building has been mainstreamed in the national education system, little is known how preschool teachers contribute to the nurturance of tolerant young children as future global citizens. This study explores priority sustainable character values and their building strategies in counselling practices of pre-school teachers in West Java Province of Indonesia. Analysis of questionnaire, classroom observation and interview results by criteria of Global Citizenship Education (UNESCO, 2017) and character education in the 21st century of Bialik, Bogan, Fadel and Horvathova (2015) show that counselling topics of the participating teachers have included sustainable values of global partnership, independence, nationalism, integrity, and religiosity exercised through individual and team works. By involving social agencies such as parents, principals, and religious leaders, teachers involved their students in various characterbuilding activities. The study also recommends more detail indicators and activities for teachers to improve their students? sense of tolerance as future global citizens.